Trust in health information sources and its associations with COVID-19 disruptions to social relationships and health services among people living with HIV - Seth C. Kalichman; Bruno Shkembi; Moira O. Kalichman; Lisa A. Eaton (BMC, 2021)
Abstract Background SARS-CoV-2 infection (COVID-19) is potentially severe for individuals with compromised immune systems, including people living with HIV. Along with the direct health threats of COVID-19, there are disruptions to social relationships and health services resulting from mitigation efforts instituted by public health authorities. This study examined the relationship between trust in the government and trust in COVID-19 health information from the US CDC, state health departments, and social media on the experience of COVID-19 social and health services-related disruptions. Methods People living with HIV (N = 459) recruited through social media advertisements and chain referrals completed confidential surveys delivered through an online platform. Results Participants experienced high-levels of disruptions to social relationships and health services attributable to COVID-19 mitigation efforts. We also observed high-rates of inaccurate information and low-levels of trust in government and sources of COVID-19 information. Greater disruptions to social relationships were predicted by more concern about oneself and others contracting COVID-19, whereas disruptions to health services were predicted by greater concern for oneself contracting COVID-19, greater general medical mistrust, and less trust in information from the CDC. Conclusions Findings have implications for the necessity of rebuilding public trust in credible sources of health information and stepping up efforts to counter sources of inaccurate information.